Effect of cooking and canning on digestibility and antioxidant potential in chickpea (Cicer arietinum) and pigeon pea (Cajanus cajan) - GOSWAMI, DEEPANYETA; R, Dinesh Kumar; BANSAL, NAVITA; G, RAMA PRASHAT; C, BHARADWAJ (The Indian Journal of Agricultural Sciences, 2021)
Pulses because of their high protein content, have the potential for improving nutritional status and combating malnutrition. A study was carried out at ICAR-Indian Agricultural Research Institute, New Delhi during 2019-20 to see the effects of cooking (boiling) and canning on protein digestibility and antioxidant potential on two contrasting genotypes of chickpea (Cicer arietinum L.) and pigeon pea [Cajanus cajan (L.) Millsp.] for total protein content. The protein quality was assessed on the basis of essential amino acid score and protein digestibility in terms of Protein Digestibility-Corrected Amino Acid Score (PDCAAS). A pepsin-trypsin-chymotrypsin digestion followed by ninhydrin assay was performed to determine the digestibility. The seeds were boiled and canned in a canning solution of brine solution containing 1.3% (wt/vol) NaCl and 1.6% (wt/vol) sugar. PDCAAS (%) was higher in ’high’ protein containing lines than ’low’ protein containing lines in case of chickpea. However, no significant variation in PDCAAS % was found between ’low’ and ’high’ protein pigeon pea genotypes. The antioxidant activity (AOA) was measured by DPPH and FRAP assays and was found to increase in chickpea and pigeon pea genotypes after cooking and canning. Increased AOA in DPPH assay ranged from 62.80-94.69% and from 60.55-95.13% for the cooked and canned seeds respectively. The AOA measured by FRAP assay has shown similar results in the seeds after cooking and canning treatment which ranged from 0.82-13.42 μmol/g and from 2.63-15.71 μmol/g for cooked and canned seeds respectively. The AOA was increased in all the varieties, except in the cooked seeds of Kabuli genotypes.